The history of forensic medicine department SSMU (to the 110th jubilee) - Yu. A. Shamarin; A. S. Melchikov; A. D. Shnayder (Бюллетень сибирской медицины)
In the article there are introduced the history of forensic medicinе department, the names of its grounders, the key events of the scientific life of the department, the prospects of its development are introduced.